Intramural Gallbladder Hematoma Mimicking Gallbladder Neoplasm and The Importance of MRI in Diagnosis - Yıldırım, Mustafa; Artaş, Hakan (Bolu Abant İzzet Baysal Üniversitesi, 2022)
Intramural gallbladder hematoma is a rare cause of abdominal pain. Symptoms are generally non-specific. Therefore, imaging methods are important for diagnosis. But despite simultaneous radiological imagings, it may be difficult to diagnose a gallbladder hematoma. Because it has similar imaging findings with gallbladder neoplasm and tumefactive biliary sludge. We present a case with intramural gallbladder hematoma mimicking gallbladder tumor and its radiological findings.

Safra kesesi hematomu karın ağrısının nadir bir sebebidir. Semptomlar genellikle non-spesifiktir Bu yüzden görüntüleme yöntemleri tanıda önemlidir. Ancak eşzamanlı radyolojik görüntülemelere rağmen, safra kesesi hematomunu teşhis etmek zor olabilir. Çünkü safra kesesi neoplazmı ve tümefaktif safra çamuru ile benzer görüntüleme bulgularına sahiptir. Biz safra kesesi tümörünü taklit eden intramural safra kesesi hematomlu bir olguyu ve radyolojik bulgularını sunuyoruz.
Safra Kesesi Neoplazmını Taklit Eden İntramural Safra Kesesi Hematomu ve Tanıda MRG’nin Önemi
Keywords: Clinical Sciences; Klinik Tıp Bilimleri